2019
DOI: 10.1186/s12870-019-2172-5
|View full text |Cite
|
Sign up to set email alerts
|

A high-density genetic map constructed using specific length amplified fragment (SLAF) sequencing and QTL mapping of seed-related traits in sesame (Sesamum indicum L.)

Abstract: BackgroundSesame (Sesamum indicum L., 2n = 2x = 26) is an important oilseed crop with high oil content but small seed size. To reveal the genetic loci of the quantitative seed-related traits, we constructed a high-density single nucleotide polymorphism (SNP) linkage map of an F2 population by using specific length amplified fragment (SLAF) technique and determined the quantitative trait loci (QTLs) of seed-related traits for sesame based on the phenotypes of F3 progeny.ResultsThe genetic map comprised 2159 SNP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 104 publications
1
30
0
1
Order By: Relevance
“…Seed size (TSW) is known to have moderatehigh heritability in sesame (Uzun et al, 2013;Kalaiyarasi et al, 2019), as was found in the current study (0.88) and other crops, such as wheat (Sukumaran et al, 2018) and pea (Pisum sativum L.; Huang et al, 2017), was associated with only one region in 2020, with no overlap with SNPP and SYPP. Likewise, a small number of associated loci for TSW were found in bi-parental sesame populations (Du et al, 2019;Teboul et al, 2020), which may suggest that this trait is under less complex genetic control or under the regulation of many small-effect genomic regions. The absence of significant genomic signs for TSW (as well as other traits in the current study) indicates that other approaches, such as genomic prediction (Crossa et al, 2017), may contribute to understanding its genetic basis.…”
Section: Genetic Architecture Of Agronomical Traits Reveals Hotspot Of Overlapping Genomic Regionsmentioning
confidence: 99%
“…Seed size (TSW) is known to have moderatehigh heritability in sesame (Uzun et al, 2013;Kalaiyarasi et al, 2019), as was found in the current study (0.88) and other crops, such as wheat (Sukumaran et al, 2018) and pea (Pisum sativum L.; Huang et al, 2017), was associated with only one region in 2020, with no overlap with SNPP and SYPP. Likewise, a small number of associated loci for TSW were found in bi-parental sesame populations (Du et al, 2019;Teboul et al, 2020), which may suggest that this trait is under less complex genetic control or under the regulation of many small-effect genomic regions. The absence of significant genomic signs for TSW (as well as other traits in the current study) indicates that other approaches, such as genomic prediction (Crossa et al, 2017), may contribute to understanding its genetic basis.…”
Section: Genetic Architecture Of Agronomical Traits Reveals Hotspot Of Overlapping Genomic Regionsmentioning
confidence: 99%
“…Flavonoids represent the main secondary metabolites that influence plant seed coat color [ 46 ]. Du et al [ 28 ] mapped 14 QTL and uncovered 155 candidate genes for sesame seed coat color that were enriched principally in two pathways, diterpenoid biosynthesis and oxidative phosphorylation. Other studies in sesame detected that two major genes with additive-dominant-epistatic effects plus polygenes with additive-dominant-epistatic effects control the seed coat color, and several other major QTL have been identified [ 25 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The gene SIN_1016759/PPO had been reported as the candidate gene for black seed coat development in sesame [ 24 , 26 ]. It was also included in the list of sesame seed coat candidate genes reported recently by Du et al [ 28 ]. In plants, browning reactions on seed coat pigments are often induced by the oxidation of phenolic compounds by polyphenol oxidases (PPO) such as laccases and tyrosinases and result in melanin formation mostly [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few mapping and marker-assisted selection studies have also been conducted with the use of AFLP markers for the closed capsule mutant trait [ 26 ]; RAPD markers for corolla color [ 27 ]; and SSR markers for determinate growth habit [ 12 ], male-sterile gene [ 28 ], and oil and protein content [ 2 ] to improve the efficiency of sesame breeding programs. A large number of single nucleotide polymorphisms (SNPs) have also been identified with the advent of next-generation sequencing technology and have been used for the exploitation of genetic diversity [ 29 , 30 ], the construction of high-density linkage mapping [ 31 , 32 , 33 ], and the identification of candidate genes for the improvement of sesame production [ 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%